Zapisy testamentowe i darowizny na cele dobroczynne w guberni kaliskiej 1865–1914 - Tomaszewicz, Andrzej (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
Among the various forms of help taken by the people of the Kingdom of Poland to support the poor and the sick as well as not very well-off students, testamentary legacies and donations were of great significance. In sources dating from 1865 to 1914, information about 170 such legacies intended to serve different charity purposes across Kalisz Province have been found. 1.2 million roubles have been received from these legacies. There were representatives of gentry, the intellectuals, merchants and wealthy craftsmen among the legators. However, it was the representatives of grand industrial bourgeoisie, mainly of German and Jewish descent, who have made the most substantial legacies. Owing to the charity legacies, many valuable initiatives could be accomplished. In 1899, a Henryk Schlöesser’s House of Gratuitous Apartments and Support was opened in Ozorków. In 1909, a House of Love of God and Neighbour for poor members of Evangelical Church was built in Kalisz and in 1911 a shelter for the Israelites was opened. Legacies by private individuals contributed to opening hospitals in Koło and Warta. Also, several educational institutions emerged in Ozorków, Kalisz, Konin, Wieluń and Lisków. In a situation when Polish people could not expect financial help from the occupant’s administration, the creation of several shelters and educational institutions as well as emergency help for the poor appeared to be an issue of tremendous importance.